KESEJAHTERAAN KELUARGA DAN KUALITAS LINGKUNGAN PENGASUHAN PADA ANAK USIA PRASEKOLAH - Elmanora, Elmanora; Hastuti, Dwi; Muflikhati, Istiqlaliyah (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2015)
The aim of the research was to analyze the influence of child characteristics, family characteristics, and family welfare on quality of home environment on preschool aged children. The samples involved 120 formal and nonformal preschool age children in Sungai Penuh District, Jambi Province that were chosen by stratified random sampling. Data was collected by interview and observation, and also was analyzed by descriptive analysis, correlation test, and multiple linear regression test. Based on poverty line indicator, families were divided into welfare families and nonwelfare families. The results showed that 45,8% families was welfare and 54,2% families was nonwelfare. The quality of home environment was measured by scale of Home Observation for Measurement of the Environment (HOME) and was divided into good and less. Parent provided language stimulation, responsivisity, and modeling into good quality, while the availability of learning materials, physical environment; academic stimulation, variety of stimulation, and acceptance into less quality. The quality of home environment was influenced by child’s age and sex, family size, maternal education, and family welfare.